Genome-based characterization of AHPND and non-AHPND Vibrio campbellii isolates from Republic of Korea - Lee, So-Young; Choi, Hee-Jae; Lee, Seonhyun; Choi, Jaeyoung; Kwak, Jun Soung; Kang, Yue Jai; Hong, Sung-Chul (Frontiers in Microbiology, 2026)
With mounting evidence that Vibrio campbellii can act as a causative agent, acute hepatopancreatic necrosis disease (AHPND) represents a serious threat to global shrimp aquaculture. In this study, we present a comparative genomic analysis of 101 V. campbellii strains, including the recently isolated pathogenic and non-pathogenic strains, V. campbellii HJ-2023 and V. campbellii HJ-2023n, from the Republic of Korea. Whole-genome sequencing revealed that the pathogenic strain harbors three plasmids and carries the canonical AHPND toxin genes pirA and pirB, along with an expanded repertoire of virulence and secretion system genes. Pan-genome and insertion sequence analyses showed that pathogenic strains tend to cluster based on shared mobile genetic elements, particularly transposases located near toxin genes, underscoring the role of horizontal gene transfer in virulence acquisition. Although all strains displayed a broad distribution of antibiotic-resistance genes, pathogenicity did not consistently correlate with their presence. Similarly, carbohydrate-active enzyme (CAZyme) profiles were largely conserved, although certain enzymes, such as chitinases, may contribute accessory functions in host invasion. Notably, the AHPND-associated V. campbellii HJ-2023 strain contained multiple copies of key T6SS and T1SS genes, suggesting an increased potential for toxin delivery. These findings suggest that pathogenic potential in V. campbellii likely arises not only from the presence of toxins but also from the complex interplay of mobile elements, secretion systems, and genomic architecture. This study provides an essential genomic framework for understanding the emergence of AHPND in V. campbellii and offers insights to enhance molecular diagnostics, strengthen biosecurity, and improve disease control strategies in shrimp aquaculture.